2021
DOI: 10.1107/s2059798320015405
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio determination of the shape of membrane proteins in a nanodisc

Abstract: New software, called Marbles, is introduced that employs SAXS intensities to predict the shape of membrane proteins embedded into membrane nanodiscs. To gain computational speed and efficient convergence, the strategy is based on a hybrid approach that allows one to account for the contribution of the nanodisc to the SAXS intensity through a semi-analytical model, while the embedded membrane protein is treated as a set of beads, similarly to as in well known ab initio methods. The reliability and flexibility o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 79 publications
3
3
0
Order By: Relevance
“…S10 to 16) because the membrane is fluid at room temperature and large compared to the protein. Similar behavior has been proposed based on results from small-angle scattering and cryo-TEM (42,43). In particular, we provide support that the roughly triangular features discernible in many frames (Fig.…”
Section: Resultssupporting
confidence: 89%
“…S10 to 16) because the membrane is fluid at room temperature and large compared to the protein. Similar behavior has been proposed based on results from small-angle scattering and cryo-TEM (42,43). In particular, we provide support that the roughly triangular features discernible in many frames (Fig.…”
Section: Resultssupporting
confidence: 89%
“…Although the prevailing concept suggests that the MPs are predominantly localized in the central region of the nanodisc surrounded by the lipid molecules, this depiction may inaccurately imply that the protein is passively floating in the lipid environment. On the contrary, our collective observations revealed a more dynamic behavior, supporting previous observations of an entropic-driven migration of MP toward the nanodisc edge (López et al 2019;Orioli et al 2021).…”
Section: Membrane Proteins Have a Spatial Preference Toward The Edge ...supporting
confidence: 91%
“…Our analysis focused on the structural heterogeneity in nanodiscs, which revealed that nanodiscs possess structural fluidity and that MPs move laterally within the nanodiscs. This behavior has been observed previously in silico (López et al 2019;Orioli et al 2021). Kern et al also experimentally observed interactions between SARS-CoV-2 ORF3a and MSP in the nanodisc environment (Kern et al 2021).…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…MPBuilder constructs atomistic models of membrane-mimicking systems and covers the cases of MSP or Salipro nanodiscs as well as detergent belts and bicelles; however, it also needs an atomic model of a membrane protein as the input data. The third approach is realized in the Marbles program [ 156 ]; it predicts the shape of membrane proteins embedded into nanodiscs using a hybrid approach that accounts for nanodiscs’ contribution to the SAXS intensity through a semianalytical model, while the embedded membrane protein is treated as a set of beads, similarly to as in well-known ab initio methods. Today, Marbles is the only approach for ab initio shape determination of MPs reconstituted in nanodiscs, and it combines shape determination with a search for the position of the protein in the nanodisc.…”
Section: Applications Of Lipodiscs In Structural Biologymentioning
confidence: 99%